Acute effect of caffeine supplementation on performance of muscular strength and cardiovascular changes during resistance training - W. Materko; E.L. Santos (Desafio Singular, 2011)
The purpose of the present study was to evaluate the acute effect of caffeine on the muscular strength performance in addition to the possible hemodynamic changes during a strength training session. Thirteen strength training experienced male subjects were submitted to a protocol of three sets of 10RM for bench press (BP), pull press (PP), leg extension (LE) and leg curl (LC), according to three conditions: no supplementation (C); 250 mg of caffeine supplementation (S); placebo (P). All subjects were submitted to an anthropometric evaluation, followed by a 10RM familiarization test. Hemodynamic measurements - heart rate (HR) and blood pressure (BP) - were carried out before, during and after each session. Holding 48 hours time intervals, participants were submitted to three randomly presented 10RM tests according to C, S and P conditions. For conditions S and C, significant differences were found in BP and LE. No significant differences in HR and BP were found. Results seem to suggest an ergogenic effect of caffeine on submaximal muscle strength during a session of strength training.